The Effect of Problem Based Learning Integrated E-Books to Improve Learning Motivation in Physics for High School Students - Rahmasari, Alifia Azis; Zulaikha, Dewi Fairuz; Pujianto, Pujianto; Jumadi, Jumadi (Jurnal Pendidikan Progresif, 2022)
The Effect of Problem Based Learning Integrated E-Books to Improve Learning Motivation in Physics for High School Students. Objectives: This study aimed to determine the effect of problem based learning integrated e-book to increase physics’ learning motivation of high school students. Methods: A quasi-experimental design with a pretest-posttest control group design. The research sample was taken using a random sampling technique. The sample consisted of 68 students in grade XI of State Senior High School in Randudongkal, Indonesia. They were divided into two classes, namely 34 students in the experimental class and 34 students in the control class. The students' learning motivation was measured through a questionnaire instrument based on the ARCS aspect through the google form. Findings: The results of the paired t-test analysis of motivation to learn physics in the experimental class showed a significant value with the sig 0.000. Conclusion: This showed that the use of e-books was effective in increasing students' motivation to learn physics. Keywords: physics’ e-book, problem based learning, physics’ learning motivation.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202213